(3aJGhi SCd YfgG GdCPQYi hGdCLhHI YdjgGs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf HGdLhGH Yf gPg GdeSGFd hHjGf eG Nai efgG Ydjg ajgG ef GdOdGFd aEf efgG eG YeJ Hg GdHdhi GdeSFdI GdChdi bGd GdTjN fLe GdOjf QMeg Gddg ai GdcaGjI Gf HjY GdLRQ hGdSdLe s
(3BNQgG (B:s
(3bO ETJed Ydi UhQ hde jaQOgG dCUMGH Hd PcQhgG eOQLI eY GdbSe GdQGHY aGdMGQjI GdeCNhPI Ydi gPg GdUhQI ajgG gPG GdNdGa hGLJfGHgG eMd GdhQY JeJ GdeSGFd GdedbH hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1223s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B896s
Keywords: (3Gdabg GdESdGejs